Software educativo y su incidencia en el proceso de enseñanza aprendizaje para los estudiantes de bachillerato general unificado en la asignatura de informática aplicada de la unidad educativa león de Febres Cordero de la Parroquia San Juan, cantón Puebloviejo - Vera Manzo, Martha Gabriela (2017)
The intended study is to implement the technology through an educational software of mathematics in the teaching-learning process so that students assimilate the knowledge imparted by the teacher in a more active and dynamic way, thus improving their academic performance. This research involved a sample of 144 students. The research model that was used is the feasibility study by determining the chi square, leaning against a field investigation of documentary and bibliographical character, the same that allowed the axiological, educational, philosophical and technological foundation. The results obtained are related to the objectives, and by which the proposal was raised specified in Chapter IV of this investigation, thus determining the importance of a manual for use of GeoGebra educational software, the same that will provide the teacher and student ease of making mathematical calculations in a shorter time and with a margin of error of 0% time.